Factors Contributing to Diagnosis and Prognosis in Sinonasal Malignancies - Wenjing Li; Jianqiang You; Haixiang Xue; Changjiang Chao (Journal of Immunology Research)
Objectives. This study was intended to explore and analyze the factors which affect the survival and prognosis of patients with malignant tumors of nasal cavity and sinus. Methods. Retrospective analysis was performed on the clinical data of 39 cases of malignant tumors of nasal cavity and sinus that met the requirements of the study. A follow-up study was performed on the patients for more than 36 months. Survival analysis was conducted via the Kaplan-Meier method and log-rank test. Cox regression model was used for multivariate analysis. Results. Gender, pathological type, treatment plan, clinical stage, and survival time of patients were different. Clinical stage was substantially related to the survival of patients (P<0.05), which was an independent factor affecting prognosis. Conclusions. Early detection and comprehensive treatment of sinonasal malignancies can improve the prognosis and prolong the survival time of patients.